A review of research on diseases and pests of almonds in Morocco - Boulif M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In Morocco, almonds cover 151 Kha producing 19.8 Kt of shelled nuts. This makes almonds rank 2nd after the olives in terms of area covered. Due to its rusticity, the almond tree is found in various ecological zones throughout Morocco, generating additional income to small farmers operating on marginal lands. The major diseases attacking almond orchards in Morocco are Monilia blossom blight (Monilia laxa), leaf curl (Taphrina deformans), anthracnose (Gleosporium amygdalynum) and shothole (Coryneum beijerinkii) while crown gall (Agrobacterium tumefasciens), nematodes (Meloïdogyne spp.) and Phytophthora root rot may occur in almond nurseries. The most prevalent pests on almonds remain the mites (Tetranychus spp., Briobia rubrioculus), the aphids (Myzus persicae, Brachycaudus amygdalinus, Hyaloperus pruni) that attack the foliage of almond, older and stressed almonds trees are subject to the attack of the Flat-headed Root Borer (Capnodis tenebrionis) and the bark beetles (Scolytus amygdali). While fungal diseases can be easily controlled through appropriate fungicidal sprays during critical periods, the flat-headed root borer and the bark beetle remain uncontrolled because of lack of registered appropriate pesticides that are cost effective to be used by the farmers. The Green Morocco Plan (Plan Maroc Vert) initiated in 2008 to enhance agricultural production in Morocco and ensure food security of the country, has opted for extending almond plantations to valorize marginal lands, thereby increasing farmers income while preserving soils from erosion in these areas. To ensure the success of the new plantations, certified disease and pest-free almond nursery stocks are promoted within the Green Morocco Plan.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)